E-Wallet adoption: A case of youth customers’ acceptance / Faiznur Aiza Hani Muhammad Fozi, Hamizah Zailan and Nur Syamira Hanim Saidi - Muhammad Fozi, Faiznur Aiza Hani; Zailan, Hamizah; Hanim Saidi, Nur Syamira (2021)
E-Wallets are prepaid wallets that require the user’s money to be loaded prior to make any transaction. It provides quick connection with the banks to develop banking application activities. The problems identiﬁed for this paper is people who still skeptical with the use of technologies in making payment such as debit payment, online banking payment, mobile payment and more. The aims of this paper are to measure the level of acceptance of e-Wallet application among youth customers and to investigate the factors contribute towards e-Wallet acceptance among youth customers. Online questionnaire was used for the data collection method in this study. The target population used in this study were all youth customers who used e-Wallet. The minimum sample size for the youth customers that use e-Wallet was 150 samples. The SPSS software was used for statistical analysis. SPSS shows data analysis for descriptive statistics, prediction of numeral outcomes, data transformation, graphing, and direct marketing features. Reliability for each item was accomplished in SPSS. The result shows that all the variables have a strong reliability. The factors that are related to youth customers’ acceptance of e-Wallet that are checked by the Structural Equation Modeling (SEM) indicate that all the factors affect the youth customers’ acceptance of e-Wallet. The youth customers’ acceptance of e-Wallet are affected by convenience, credibility and attractiveness of alternatives of using e-Wallet.